Os copépodes na região de Cabo Frio: variação qualitativa e quantitativa, durante um ciclo de ressurgência, Rio de Janeiro, RJ, Brasil - Ribas, Wanda Maria Monteiro (1988)
The aim of this dissertation was to study the qualitative, quantitative and synecological aspects of the copepod population of the coastal water at Cabo Frio. During six days, in the period more probable for upwelling, plankton were colected every four hours at one fixed station using two methods: a) vertical trawl to study the mesozooplankton and b) collection with van Dorn bottle to study the microzooplankton. FFifty five copepod species were identified. Paracalanus parvus, Calanoides carinatus, Oithona plumifera, Oncaea media e Temora stylifera were the most abundants. Quantitatively, tall size classes copepods contributed to the zooplanktonic richness of the waters. Larval stages, as nauplius and copepodid, had values up to 35.000 ind. m-3 and the ·adults up to 1.500 ind. m-3. The population structure was characterized by a higher number of females than males and a specific diversity around 2 bits. ind-1. The recruitment of copepods (higher ocurrence of larvae) seemed to be more intense in coastal waters. The thermic gradient (thermocline) revealed to be an important factor in the copepod distribution, mainly on Temora stylifera and phytoplankton biomass (chlorophyll) was a determinant factor on the development of Paracalanus parvus, the most abundant herbivorous species at Cabo Frio. Calanoides carinatus was more abundant when the surface waters standed off from the coast (upwelling). Three species groups with the sarne ecological characteristcs were identified: spec1es present all over the period, typical species of upwelling and oceanic species related to superficial heating.